The Psalms of Lament and the Mental Health of the Congregation: A Biblical-Pastoral Approach - Adi, Ilham (Cattleya Darmaya Fortuna, 2025)
This study tested the effectiveness of operationalizing the Psalms of Lament as a trauma-sensitive biblical-pastoral intervention for congregational mental health. Using a quasi-experimental mixed-methods design with a convergent embedded model, the study was conducted with two groups of congregations (intervention vs. passive control) during 4–6 structured lament liturgy sessions that included: (1) invocation and naming of grief, (2) petition/protest of faith, (3) remembrance of God's faithfulness, and (4) communal closure. Primary indicators were measured using the anxiety-depression summary scale (PHQ-4), while secondary indicators included spiritual hope and communal connectedness (Likert scale 1–5). Qualitative data were obtained from lament journals, facilitator notes, and interviews/FGDs, then analyzed thematically and integrated into quantitative findings through joint displays. Results showed a greater reduction in psychological symptoms in the intervention group compared to the control group, accompanied by an increase in spiritual hope and a sense of communal connectedness. The effect size for the comparison of changes between groups was moderate, and no serious adverse events were observed; adherence (≥4 sessions) was associated with greater improvement. Qualitative analysis confirmed two key mechanisms: a safe space for naming difficult emotions and a repositioning of the meaning of suffering within the horizon of faith through remembrance of God's faithfulness. These findings confirm the legitimacy of lament liturgy as a healing worship practice that can be inculturated in the Indonesian context across denominations. Limitations include the non-randomized design, community sample size, and reliance on self-report. Further research with group/congregation-level randomization and longer follow-up is recommended to strengthen causal inferences.